THE EFFECT OF SOCIAL MEDIA ON CONSUMER’S DECISION PROCESS OF PURCHASE: A CASE OF ELAZIG PROVINCE - Nurcan YÜCEL (Fırat University, 2019)
The importance of social media has enormously increased with the development of internet and communication technologies. Especially, social media attracts enterprises and consumers interest as a result of its existence in every aspect of human life and its presentation of various advantages. Accordingly, a research model was developed in order to determine what kind of effect it has on perception, attitude and purchasing behavior in consumer purchase decision process. For testing the research model, a survey was made with 700 people. The research sample consists of people, age 18+, who live in the 37 different neighbourhoods in Elazig. The first and second part of the study, literature review has been done in terms of the social media marketing and the effect of social media on consumer purchase decision process. Also, in the third part, a research has been conducted about Elazig province to analyze the effects of social media on consumer purchase decision process. As a result of this study, it is found out that there is a relation between consumers’ social media usage and sharing their perception towards social media, their attitudes towards social media, their purchasing behavior and lastly their experinces through social media.